(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Objectives: This research investigates the impact of projects on the development of productive families in the holy city of Makkah, emphasizing the significance of economic growth as a vital requirement for contemporary community life. The study aims to identify factors that enhance the productivity and economic growth of these families while providing practical recommendations to increase their contributions to the economy. Methods: The study employs a descriptive analytical methodology, utilizing questionnaires and interviews to collect data from a sample of productive families across various neighborhoods in Makkah. The research also includes a preliminary pilot study to ensure the quality of the data collection tools. Results: The findings reveal that effective program facilitation, access to financial support, and training initiatives significantly contribute to the economic development of productive families. Challenges such as limited access to resources, market competition, and insufficient marketing strategies persist, hindering the growth of these families. Conclusions: The research concludes that despite the recognized potential of productive families in boosting the local economy, substantial challenges remain. It stresses the need for enhanced support from governmental and private sectors to empower these families, including better access to funding, training programs, and effective marketing strategies to facilitate their economic participation and sustainability in Makkah.